ЎҚУВ-ТАРБИЯ МАЙДОНИ ВА УНДА ЎҚИТУВЧИ ФАОЛИЯТИНИНГ ЎЗИГА ХОС ХУСУСИЯТЛАРИ - Даўлетмуратова, Э.; Ильясова, З. (SCIENCE and SOCIETY, 2016)
Greative potential of a teacher is based on his innovative activity and it raises efficiency of reforms in education. In this article the author has proved the importance of creativity of a teacher and described some ways of improving pedagogical creativity. This article deals with organizing pedagogic and managing peculiarities in the system of continuous education. There is discussed the factors improving offectiveness in the process of education and the issues of training and stages of holding experienced-experimental work in the system continuous education in the Republic of Uzbekistan.
Keywords: pedagogical experimental works; program of experienced and experimental works; hypotheses; actions of the experimenter; productivity